Graphene reinforced polymer matrix composites using 3D printing - Mohammad Haiqal Amirul Mohammad Yazid (Nanyang Technological University, 2022)
This study seeks to to manufacture, characterise and compare nacre-like reinforced nylon composites. The nacre-like reinforcement shall be graphene. The composites printed will be of four different series which are nine, six, three and one layer of grapehene. Samples will be printed using novel hybrid manufacturing method, with nylon as the filament and 5 wt.% graphene ink as the precursor for graphene. Composite samples were printed into four different series; nine, six, three and one layer graphene composites. Each series had five samples. Five nylon samples were printed at 0.1mm layer height. Samples were then post processed prior to tensile tests.